GENDER-SPECIFIC DIFFERENCES OF CARDIAC VEGETATIVE CONTROL IN ADRENALINE-INDUCED NECROSIS AND LIGHT DEPRIVATION - Bezkorovaina, H. O.; Klishch, I. M.; Khara, M. R.; Pelykh, V. Ye. (International Journal of Medicine and Medical Research, 2020)
Background. Cardiovascular disease is the main cause of morbidity predominantly in males. Stress is one of the crucial factors, especially with light desynchronosis. Objective of the study was to assess gender-specific characteristics of cardiac vegetative control in myocardial necrosis in cases of light deprivation. Methods. Cardiac vegetative control in adrenaline-induced myocardial necrosis (AIMN) in a setting of light deprivation (LD) was assessed in 72 mature white rats of both sexes. The animals were divided into 2 groups: G1 – the animals kept under day/night cyclic balance (12 hours/12 hours); G2 – the animals kept at LD (illumination 0.5-1 LX) for 10 days. On Day 11, AIMN caused by adrenaline (0.5 mg/kg) and heart rate variability (HRV) was assessed in 1 hour and 24 hours. Results. The development of AIMN at LD in the ♂G2 led to HRV increase that was caused by augmentation of parasympathetic and reduction of sympathetic cardiac effects. In cases of AIMN, changes of CVC in the ♀G2 were similar to the ♀G1. However, in 1 hour of AIMN, parasympathetic cardiac effects were more significant than in the ♀G1. While the ♀G2 AIMN animals experienced balanced sympathetic and parasympathetic actions, the predominance of the sympathetic component was evidenced in the ♀G1 AIMN animals. Conclusions. Light deprivation has different effects on baseline sympathetic/parasympathetic balance in males and females, i.e. increased parasympathetic control of heart rhythm in males and maintenance of sympathetic/ parasympathetic balance in females.